Innovative Strategies and Challenges in Local Treasury Operations: A Policy-Oriented Study in The Province of Albay - Flores, Brenda; Gonzales, Maria Luisa (JPAIR Multidisciplinary Research, 2026)
The post-pandemic world has accelerated the global shift towards digital governance, placing unprecedented emphasis on the modernization of local treasury operations (LTO). Studies by the International Monetary Fund (IMF, 2022) highlight the urgent need for governments to leverage digital technologies to enhance revenue mobilization and fiscal transparency. The IMF's Fiscal Monitor reports emphasize that digital transformation, when implemented effectively, can significantly improve tax administration and reduce corruption risks. This mixed-methods study explores the innovative strategies and operational challenges within the treasury offices of Legazpi, Ligao, and Tabaco in the Province of Albay. Findings reveal a "fiduciary-operational paradox," where high regulatory compliance is maintained despite a core-infrastructure bottleneck: 65% of treasury functions remain manual and 90% of the workforce lacks specialized IT competencies. Statistical analysis using the Kendall Coefficient of Concordance (W) demonstrated a significant and unanimous provincial consensus among respondents regarding the prioritization of modernization strategies, indicating high institutional readiness for reform. To bridge the gap between regulatory compliance and operational efficiency, the study proposes the Albay Resilient Treasury Modernization (ARTM) paradigm. This five-pillar policy intervention institutionalizes digital standards, mandates competency-based human resource development, and integrates disaster risk financing into local law. These findings provide a scalable framework for Local Chief Executives to enhance revenue generation and foster sustainable, technology-driven governance in the Philippines.
Keywords: Public Administration; Local Government Units (LGUs); Fiscal Management; Public Policy; Albay; Treasury Operations; Revenue Innovation; Philippines